2018
DOI: 10.1111/ijfs.13880
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolaemic and hepatoprotective effects of virgin avocado oil in diet‐induced hypercholesterolaemia rats

Abstract: Summary Hypercholesterolaemia is a chronic disease associated with the development of nonalcoholic fatty liver disease and atherosclerosis. This study aimed to investigate the hypocholesterolaemic and hepatoprotective effects of virgin avocado oil (VAO) using diet‐induced hypercholesterolaemia rats. Male Sprague Dawley rats were fed high‐cholesterol diet for 4 weeks to induce hypercholesterolaemia. After confirming the establishment of hypercholesterolaemia model, the VAO (450 and 900 mg kg−1 body weight per d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
(53 reference statements)
1
15
0
1
Order By: Relevance
“…The histopathological evaluation of liver and kidney of the experimental mice in this study revealed that daily oral administration of CELE for 28 days at 1000 mg/kg dose resulted in various hepatic and renal lesions. The significant hepatic degeneration and necrosis observed histopathologically in the group of mice administered with daily oral doses of CELE at 1000 mg/kg for 28 days were suggestive of toxic or adverse effects [ 7 , 50 , 51 , 68 , 69 , 70 ] of the extract on the animals, as earlier observed in the results of plasma biochemical parameters for hepatic injury markers (ALT and AST). Similarly, the renal tubular degeneration and necrosis observed in this research further supported the results of plasma biochemical parameters, providing further indication that administration of the extract at 1000 mg/kg is not safe [ 50 , 51 ] for the female ICR mice.…”
Section: Discussionsupporting
confidence: 66%
“…The histopathological evaluation of liver and kidney of the experimental mice in this study revealed that daily oral administration of CELE for 28 days at 1000 mg/kg dose resulted in various hepatic and renal lesions. The significant hepatic degeneration and necrosis observed histopathologically in the group of mice administered with daily oral doses of CELE at 1000 mg/kg for 28 days were suggestive of toxic or adverse effects [ 7 , 50 , 51 , 68 , 69 , 70 ] of the extract on the animals, as earlier observed in the results of plasma biochemical parameters for hepatic injury markers (ALT and AST). Similarly, the renal tubular degeneration and necrosis observed in this research further supported the results of plasma biochemical parameters, providing further indication that administration of the extract at 1000 mg/kg is not safe [ 50 , 51 ] for the female ICR mice.…”
Section: Discussionsupporting
confidence: 66%
“…Up to now, avocado oil has been scientifically proven for its effectiveness on osteoarthritis treatment, wound healing, and anti‐diabetic . The hypocholesterolemic and hepatoprotective properties of avocado oil have been reported in our recent study . These associated health benefits are attributable to the properties of avocado oil where it does not contain cholesterol and trans‐fatty acids, while rich in unsaturated fatty acids (oleic and linolenic acids), tocopherols and bioactive phytochemicals such as phytosterols, carotenoids, and polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…Functional compounds from avocado waste have shown an antioxidant effect through the reduction of pro-oxidative substances ( 26 28 ): hepatoprotective, gastroprotective, lipid-lowering, and hypoglycemic effects ( 8 , 9 , 15 , 29 ). Other studies had evaluated some of its effects in vitro on human colon cancer cells ( 30 , 31 ), on gut health in rats ( 32 ), and on hypercholesterolemic rats ( 33 , 34 ). Some others have been related to cognitive function such as improvement in learning and memory processes in subjects exposed to diets high in fat and sugars ( 14 , 16 ).…”
Section: Introductionmentioning
confidence: 99%